2013
DOI: 10.14233/ajchem.2013.13416
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Some Properties of Polypropylene Based Nanocomposites Made Using Almond Shell Flour and Organoclay

Abstract: Natural fibers reinforced polymers, known as FRPs, have received a great deal of attention during the past decades 1,2. FRPs include lignocellulosic materials, such as wood, hemp, linens, corns stalks, coconut shells, peanuts shells, almond shells, wheat and rice straws, etc., as fiber or filler and thermoplastic or thermoset polymers as a matrix. Although the use of natural fibers is not as popular as the use of mineral or inorganic fillers, it has several advantages over traditional fillers and reinforcing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Lignocellulosic materials have been used as fillers in the thermoplastic industry for the replacement of conventional synthetic fibers, such as aramid and glass, because of their low density, good thermal insulation and mechanical properties, reduced tool wear, unlimited availability, low price, and problem-free disposal (Bledzki and Gassan 1999;Mishra et al 2001;Belgacem and Gandini 2008;Ghasemi and Farsi 2010;Ayrilmis et al 2013;Lashgari et al 2013;Salmah et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lignocellulosic materials have been used as fillers in the thermoplastic industry for the replacement of conventional synthetic fibers, such as aramid and glass, because of their low density, good thermal insulation and mechanical properties, reduced tool wear, unlimited availability, low price, and problem-free disposal (Bledzki and Gassan 1999;Mishra et al 2001;Belgacem and Gandini 2008;Ghasemi and Farsi 2010;Ayrilmis et al 2013;Lashgari et al 2013;Salmah et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Since the almond shell has no important industrial value, it is normally incinerated or dumped. It is a waste material in western Iran, generated during nut processing and usually burnt (Lashgari et al 2013). Previous studies (Pirayesh and Khazaeian 2012;Lashgari et al 2013;García et al 2014) reported that almond shell flour (ASF) could play an important role in the manufacture of filled thermoplastic composites and wood-based panels, thereby reducing the demand for wood material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Almond Shell (Prunus Dulcis) is one of the most abundant and low-cost product which is available as a waste compound [2]. The almond shell has no important industrial value and it is normally incinerated or dumped [3][4]. It was reported that almond shell flour could play an important role in the fabrication of filled thermoplastic composites and wood-based panels, thus reducing the requirement for wood material [3,5].…”
Section: Introductionmentioning
confidence: 99%